The impact of chlorine, ultraviolet-C, and microwave treatment on the survivability of Blastocystis sp. cysts - Amira B. Mokhtar; Panagiotis Karanis; Chad Schou; Shahira A. Ahmed (IWA Publishing, 2023)
Blastocystis sp. is a common widely distributed gut protozoan, with water transmission identified as one of its transmission routes. This study aimed to investigate the effect of chlorine, ultraviolet (UV)-C, and microwave (MW) treatments on the in vitro viability of cysts of Blastocystis sp. Purified Blastocystis sp. cysts were molecularly subtyped. Viable cysts were subjected to different free chlorine concentrations (1, 2, and 4 ppm), different doses of UV-C (5.13, 10.26, 20.52, and 40.47 mJ/cm2), and MW irradiation times (10, 15, 30, and 45 s). Viability reduction percentage, log10 inactivation, and micrometre-based optical microscopy examined cyst number and appearance after each disinfection trial. The three disinfectants' efficacy and application conditions were assessed. The analysed isolates of Blastocystis cysts were subtype 3, possessed varying sizes and shapes, but two identical genomes. The cysts of Blastocystis sp. were resistant to chlorine at all doses and exposure durations tested. UV-C at a dose of 40 mJ/cm2 and MW treatment for 15 s were able to completely disinfect the cysts. The MW was the most effective disinfectant against Blastocystis cysts based on all evaluated factors. MW irradiation is the most efficient water treatment method for eradicating Blastocystis cysts in an easy and safe manner. HIGHLIGHTS Blastocystis is a waterborne protozoan with transmissible infective cyst form.; There is a paucity of studies on water treatment methods to inactivate the cysts.; Cysts were collected, purified, subtyped, and sequenced for in vitro treatment.; Chlorine, UV-C, and microwave were assessed for their effect on cysts' viability.; Microwave was the most effective method for eradicating cysts of Blastocystis.;